2020
DOI: 10.33271/mining14.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Research into limits of gas-fired burners flame stabilization in the flue gas recirculation

Abstract: Determining the flue gas recirculation effect on the verge of the gas-fired burners flame stabilization based on experimental industrial research. Methods. The studies were conducted on a circular heating furnace with a diameter of 30 m of the Interpipe NTRP wheelrolling workshop. The furnace for blanks heating to 625 ± 25°C with their isothermal holding has 5 zones with an adjustable and systematic supply of natural gas. To increase the thermal performance efficiency, the furnace has been equipped with an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Table summarizes the values of the different flue gases involved in the definition of FGR. The portion of recirculated gas was set to 30% to reduce the combustion disturbances that could negatively affect the plant behavior . Note that during the FGR experiments, the flue gas that entered through the plenum, m ̇ 1 , was maintained as a constant value, which affected the set point of the fresh air supplied by the primary fan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table summarizes the values of the different flue gases involved in the definition of FGR. The portion of recirculated gas was set to 30% to reduce the combustion disturbances that could negatively affect the plant behavior . Note that during the FGR experiments, the flue gas that entered through the plenum, m ̇ 1 , was maintained as a constant value, which affected the set point of the fresh air supplied by the primary fan.…”
Section: Methodsmentioning
confidence: 99%
“…In solid fuel combustion, the focus was laid on coal. , Most research has discovered significant CO and NO x reductions, such as Houshfar et al, who achieved a nearly 70% decrease. According to Ivanov, the feasibility of FGR is attributed to the low economic and technical effort needed to adapt it to existing facilities, although a proper adjustment of the recirculated gas needs to be assessed since it can cause a relevant disturbance in the flame front. Some studies have focused on the plant response to different FGR portions and have reported nearly 30% reduction values for CO and NO x concentrations with 10% to 20% FGR and even further effects when the recirculation rate was raised to 30%. , …”
Section: Introductionmentioning
confidence: 99%